The `Idea of Knowing’ in Hegel’s Logic - Rinaldi, Giacomo (Philosophy & theology, 1991)
I first outline the arguments by which Hegel upholds the validity of his ‘rationalistic’ ideal of an ‘absolute knowing’, and then attempt to state precisely the sense in which such a Hegelian conception can be rightfully styled ‘idealistic’, and the reasons why it turns out to be preferable to the opposite empirical-realistic outlook. Thirdly, I examine his critique of ‘finite knowing’. Finally, I enumerate the fundamental features of that ‘speculative (i.e., strictly philosophical) knowing’ which, as the Absolute Idea, Hegel sets against ‘finite knowing’ as the higher category in which the peculiar deficiencies and contradictions of the latter are integrated and reconciled.